Milky Moo: spreading the Milk Mantra. Issue 3 (2nd May 2017) - Mohapatra, Subhalaxmi; Roy, Subhadip
Abstract : Synopsis: Srikumar Misra founded Milk Mantra as a milk producing and selling company in the state of Odisha, India in 2010. The company subsequently diversified into milk-based products such as yogurt and cottage cheese and spread its foray into the neighboring states. In 2014, the company had to overcome a few challenges from the macro environment as well as think of a marketing and communication strategy to gain competitive advantage. Research methodology: The case is based on the primary research and has been developed using interviews of the company representatives and documents made available from the company. Wherever required, written permission has been obtained from the company representatives. Relevant courses and levels: This case could be a part of the Marketing Management course in a graduate/undergraduate program in Business Management. The case could also be a part of a Brand Management or Integrated Marketing Communications course in the same program for specialized subjects such as branding a generic product or brand communications. This case could also be used for a short discussion in a distribution and logistics course. Theoretical bases: The specific topics, which could be facilitated through this case, are the 4 Ps of marketing, distribution and marketing strategy. The case also relies on the theories of branding and marketing communication.